Left ventricular dysfunction in transfusion dependent beta Thalassemia major patients in Bangladesh - Saha, Simu; Saha, Tapash; Morshed, AKM Amirul; Fatmi, Md Lutful Ehsan; Zakia, Nazneen Umme; Razzaque, SKA (Cardiovascular Journal, 2016)
Background: Thalassemia major is an inherited haemoglobin disorder resulting in chronic haemolytic anaemia. Patients with beta thalassemia major are maintained on continuous blood transfusion regimens resulting in iron overload that adversely affects both the structure and function of the heart and other vital organs which can be easily prevented with iron chelating therapy. The aim of the study was to detect left ventricular dysfunction at an early stage so that early effective intervention can be done. Methods: A total of 50 patients with beta thalassemia were included in the study by non randomized qualitative purposive sampling from July 2013 to June 2014. Their total body iron status was be assessed by doing serum ferritin level. Left ventricular systolic and diastolic function was assessed by echocardiography Results: Cardiac dysfunction was present in 11 patients with high incidence in patients with low pre-transfusional haemoglobin group (p=0.4) and in patients having high serum ferritin level (p=0.02). Systolic cardiac dysfunction was present in 7(14%) of patients and diastolic dysfunction was present in 4(8%) of patients. There was a weak but significant correlation between left ventricular ejection fraction and serum ferritin concentration (r=-0.22; p=0.03). Only few (8%) patients had diastolic dysfunction. Conclusion: Patients with beta thalassaemia on an adequate transfusion showed an abnormal left ventricular systolic function. In early stage of disease diastolic function was normal but after repeated transfusion there were impaired relaxation indicating diastolic dysfunction. These findings seem mainly to be related to chronic anaemia and serum ferritin level Cardiovasc. j. 2016; 9(1): 31-35